The exemplum in the literary and religious culture of the late-medieval Netherlands / Marcin Polkowski. - Polkowski, Marcin
Zakres i treść: questions of definition - what is an exemplum, the "Beatrijs" - a Marian legend, miracle narrative or exemplum?, exemplary lives, the homiletic exemplum, the truthfulness of exempla, exemplaria from the low countries, the spatial and temporal "journeys" of exempla collections from the low countries, middle Dutch theological, historical and parenetic texts as sources of exempla, miracula and miracle narratives, the low countries as the place of action in the exemplum, after the middle ages - the longevity of the exemplum.